Sistem Informasi Manajemen Stock Barang Menggunakan Metode Fefo : Studi Kasus : Box Cakes And Pastry Tambaksari Surabaya - Hamzah Dimas Syah Reza; Henni EndahWahanani; Retno Mumpuni (Jurnal Teknik Informatika dan Teknologi Informasi, 2024)
The development of information technology is currently growing rapidly. Many organizations and companies have implemented computerized and structured information systems to support their work. However, there are still business sectors that have not yet implemented a computerized information system, such as the bakery in Tambaksari, namely Box Cakes and Pastry, which still carries out its work manually in recording stock of goods and checking the expiration date on each item displayed. at the shop, The final result of this research is a stock management information system in which stock data recording and checking is no longer done manually but instead uses a computerized system. This system will sort expiration dates automatically by applying the FEFO method, then this system will display notifications / reminders for employees working at Box Cakes and Pastry to make it easier to find out items that are approaching their expiration date.